A SYSTEMATIC LITERATURE REVIEW OF ARTIFICIAL INTELLIGENCE USAGE AND EFFECTIVENESS IN EFL STUDENTS’ LEARNING - Devina Aulia Puteri; Emma Rosana Febriyanti; Inayati Fitriyah Asrimawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
With the recent rise of demand for an all-encompassing tool in the form of the technologically advanced Artificial Intelligence (AI), this systematic literature review examines the effectiveness of AI in the field of English learning education for English as a Foreign Language (EFL) students based on its use and effectiveness by analyzing case studies through multiple research papers and journals, guided by the PRISMA (2020) framework. Its aim is to understand Artificial Intelligence’s roles in English classroom teaching and its impact on students’ English learning. The data for this systematic review are sourced from trusted peer-reviewed websites such as Google Scholar, ERIC, and DOAJ. Through the compiled data, the finding indicates that while there are positive improvements from AI integration in EFL learners' English teaching, these studies also reported the possible limitation and negative consequences in overly using AI as a crutch in EFL students' learning. Without proper guidance from teachers and the appropriate human interaction and connection, AI could encourage bad learning habits in students. Overall, this review concludes that AI has its role in furthering English education, with its own use and effectiveness based on teachers support, appropriate task, and guideline.